Interfacial and film formation behavior of photoactive Ru(ii)bipyridyl based metallosurfactants and a rare example of a monolayer based logic gate approach - Mahato, Prasenjit; Saha, Sukdeb; Choudhury, Sipra; Das, Amitava (Chempluschem, 2012)
Three derivatives of tris(bipyridyl)–ruthenium(II) complexes with different alkyl-chain lengths (nC18H37 (1), nC14H29 (2) and nC10H21 (3)) were synthesised. All these complexes behaved as an amphiphile and their surface properties were studied at the air–water interface by measuring surface pressure–area (Π–A) isotherms. The surface morphology of the resulting films at the air–water interface was also studied by using Brewster angle microscopy. Mean molecular areas of these complexes were measured from the Π–A isotherms, which were approximately 200 Å2, thereby indicating a parallel arrangement of the Ru–bipyridyl moiety of the complexes. Mono- and multilayer Langmuir–Blodgett (LB) films were formed on different solid surfaces with transfer ratios close to one. Similarities in the absorption and fluorescence spectra of these amphiphiles in solution as well as in LB films deposited on a quartz surface confirmed the successful transfer of these films onto the substrates. The latter provided information about the arrangements of metallosurfactant molecules within the LB films. The two-dimensional concentrations of these films were calculated from the Lambert–Beer law as well as from the Π–A isotherm, which confirmed regular and reproducible transfer of the complex monolayers from the air–water interface onto the quartz surface. The surface morphology of these films on various substrates was characterised by atomic force microscopy. Furthermore, by oxidising the monolayer of complex 3, a one-input sequential logic gate was constructed.